Sleep Quality and Patterns Among Postgraduate Students of Tribhuvan University - Bhusal, Nirmal; Thapa, Nisha; Prasad, Shiva Mangal (Cognition, 2026)
Sleep is a vital physiological process essential for cognitive performance, emotional regulation, and overall well-being. University students are particularly vulnerable to poor sleep quality due to academic pressure, lifestyle habits, and excessive screen exposure. Ayurveda, the science of life regards Nidra (sleep) as one of the Tri-Upasthambha (three pillars of health), along with diet (Ahara) and regulated celibate lifestyle (Bramcharya). Disturbances in sleep are understood to contribute to imbalance in bodily humors (Doshas), especially Vata and Pitta, which may manifest as anxiety, overthinking, fatigue, reduced concentration, and mood instability. A cross-sectional study was conducted among 30 postgraduate students from various faculties of Tribhuvan University using a non-probability sampling technique to assess the patterns and determinants of sleep habits. Data were collected through a semi structured questionnaire, including the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS). Quantitative data were analyzed to determine sleep patterns and influencing factors. Poor sleep quality and irregular sleep schedules are found prevalent among postgraduate students. 43.3% of students were habitual in delayed sleep and 26.7% reported electric devices use as a major factor affecting sleep quality. The findings indicate that irregular sleep patterns, academic workload, and digital media use significantly impact sleep quality among university students. Academic stress, exam pressure, dietary irregularities, late night screen exposure and caffeine consumption emerged as major contributors to poor sleep quality. These results align with global research highlighting stress, anxiety, and electronic device use as key determinants of sleep disruption in student populations. The integration of Ayurveda-based lifestyle interventions such as regulated daily routines (Dinacharya), Yoga, reduced screen exposure, and stress management techniques could serve as holistic strategies for improving sleep health.